Generation of second-order electrochemical data for interference-free calibration of gallic acid in red wines - Montemerlo, Antonella Evelin (2022)
Wine consists of a solution of ethanol in water, which also contains a variety of organic compounds, such as organic acids, amino acids, sugars, volatile compounds and polyphenols in different concentrations. In particular, the interest in the latter is continuously growing due to its bioactive nature and its close relationship with the final qualities of the resulting product. Specifically, gallic acid is one of the most widely used phenolic compounds as a marker for the characterization of wine products.The use of sulfur dioxide is a common practice in oenology that is currently considered essential for the correct finish of wines. However, there is a growing concern about the reduction of its levels in the final product, which makes it necessary to search for complementary agents. Among the possible alternatives is ascorbic acid or vitamin C. In recent years, its use as an additive for winemaking has been reported due to its antioxidant properties, its reducing nature and because it is a healthy compound. It is important to note that ascorbic acid will never replace the use of sulfites, but it can be an excellent complement to it.The rise of multidirectional calibration enabled the quantification of numerous analytes in complex samples without interference, even in the presence of components not modeled in the calibration, commonly referred to as a second-order advantage. However, classical chemometric methodologies assume that the data comply with the property of bilinearity, which is sometimes not possible to achieve with all instrumental methods. Among them, electrochemistry is capable of providing information with high potential to be used in the development of novel second-order calibration methodologies, although they may not meet the aforementioned conditions.This work raises the possibility of developing a simple and versatile methodology for the interference-free quantification of gallic acid in the presence of ascorbic acid, based on chemometric modeling of electrochemical data. Second-order data were generated by cyclic voltammetry (CV) at different scanning speeds and various modeling strategies were implemented to treat the data obtained.The quantification of gallic acid in the presence of ascorbic acid was possible using a model based on the resolution of multivariate curves-alternating least squares (MCR-ALS). It was found that the optimal number of estimated components for calibration is equal to one. While the analytical figures of merit found, REP% 9.4, LOD 6.094x10-5 mol L-1, show the possibility of using this methodology for the quantification of gallic acid in complex samples.The studies carried out open the doors for wine quality analysis through new and innovative methodologies based on the potential of electrochemical data, combined with chemometric techniques, which make it possible to obtain results in a simple, fast and reliable way for quality control in the wine industry.